Fasting state requirements for blood sampling: a survey of patients in Cantonal Hospital Zenica, Bosnia and Herzegovina - Damira Kadić; Aida Avdagić-Ismić; Sabaheta Hasić; Ferhana Bošnjak (Medicinski glasnik, 2021)
Aim: To explore patient’s awareness and appliance of the fasting state requirements for blood sampling. Methods: This observational survey was performed at the Department of Medical Biochemistry and Immunology Diagnostics, Cantonal Hospital Zenica, from June to July 2019. An anonymous questionnaire was conducted on 200 consecutive outpatients older than 18, who were admitted to the laboratory for routine blood testing. Results: A total of 134 (67%) patients were informed that they needed to be at fasting to perform laboratory tests. Patients were mostly informed by a requesting physician or a nurse, 68 (50.8 %), and by other patients, members of the family and friends, 58 (43.3%); only seven (5.2%) patients were informed in the laboratory. A total of 75 (37.5%) patients arrived to the laboratory properly prepared. Conclusion: Most patients were not well informed about fasting state requirements for blood sampling and consequently they were not adequately prepared for laboratory tests. Laboratory should establish updated fasting recommendations available to patients and healthcare professionals, and conduct continuing education of patients and health care staff.
Keywords: blood specimen collection; diagnostic errors; patient safety; pre-analytical phase